"THE ROLE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN THE DEVELOPMENT OF UZBEKISTAN'S ECONOMY" (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the role of small business and private entrepreneurship in the development of the country's economy using various econometric models, as well as the relationship between factors related to small business and private entrepreneurship. This project aims to study the importance of small business and private entrepreneurship as important components of the economy of Uzbekistan, and to identify the specific place and role of small business and private entrepreneurship in the country's economy. In the first part of the analysis, it is determined how many main components the small business and private entrepreneurship sector has in the economy of Uzbekistan, how it is defined, and the main factors and results of development in this sector. In the following sections, a more detailed analysis of topics related to the impact of the sector on the development of the country's economy is provided. This analysis shows that it has many important initiatives, such as state policy, investment and innovation, international cooperation, population incomes, and legal issues. The analysis focused on this topic will help to study the unique capabilities and development-enhancing role of the small business and private entrepreneurship sector in the Uzbek economy and to develop the country's economic strategy.